2019
DOI: 10.1152/ajprenal.00568.2017
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation in the release of small extracellular vesicles can be normalized by vesicle number or TSG101

Abstract: Numerous candidate biomarkers in urine extracellular vesicles (EVs) have been described for kidney diseases, but none are yet in clinical use, possibly due to a lack of proper normalization. Proper normalization corrects for normal biological variation in urine flow rate or concentration, which can vary by over one order of magnitude. Here, we observed inter- and intra-animal variation in urine excretion rates of small EVs (<200 nm in diameter) in healthy rats as a series of six 4-h fractions. To visualize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 36 publications
1
33
0
1
Order By: Relevance
“…TSG101 and ALIX have been reported to play a pivotal role in the biogenesis of exosomes and to be marker proteins for exosomes [8,20]. Representative immunoblots of urinary exosomal TSG101 These data indicated that the decreased expression of renal AQP2 was accompanied by evident proteinuria in the present experimental model of nephrotic syndrome, in good agreement with a previous report [18].…”
Section: Excretion Of Urinary Exosomal Marker Proteins After Pan Treasupporting
confidence: 92%
See 2 more Smart Citations
“…TSG101 and ALIX have been reported to play a pivotal role in the biogenesis of exosomes and to be marker proteins for exosomes [8,20]. Representative immunoblots of urinary exosomal TSG101 These data indicated that the decreased expression of renal AQP2 was accompanied by evident proteinuria in the present experimental model of nephrotic syndrome, in good agreement with a previous report [18].…”
Section: Excretion Of Urinary Exosomal Marker Proteins After Pan Treasupporting
confidence: 92%
“…TSG101 is a component of ESCRT-I, and ALIX is associated with ESCRT proteins [1]. As TSG101 and Alix play important roles in the biogenesis of exosomes, these proteins have been used as markers of urinary exosomes [8,20]. In the present study, we observed that the excretion of UE-TSG101 and UE-ALIX was decreased on day 5 and increased on day 8, suggesting that the number of exosomes released into urine was increased on day 5 and decreased on day 8 [8,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs were purified from approximately 50 mL of cell culture medium collected from U87, A549, MIA PaCa-2 and HT-29 cell lines via differential ultracentrifugation, followed by lysis in a lysis buffer as previously described [18]. Protein lysates were separated by 10% sodium lauryl sulphate polyacrylamide (SDS-PAGE) gel, and then transferred onto apolyvinylidene difluoride (PVDF) membrane (Sigma-Aldrich).…”
Section: Western Blotmentioning
confidence: 99%
“…This also holds true when broadening the filter to the top 50 proteins, indicating a decrease in ALIX-positive vesicles with potential implications for vesicle formation and late endosome maturation throughout renal transplantation. Further indication for an alteration in the release of vesicles is given by the reduction in TSG101 right after transplantation as TSG was proposed as a surrogate marker for urinary vesicle number in a recent study (29).…”
Section: Discussionmentioning
confidence: 99%